Analysis of the Language Activities Content Included in the Book "Lughaty Alkhalidah" (My Immortal Language) for the Third Intermediate Grade Students in the Kingdom of Saudi Arabia in the light of Critical Thinking Skills - Layla Falah Salem Alomrani (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The purpose of this study is to analyze the level of inclusion of critical thinking skills in language activities of the book "My Immortal Language", for third intermediate grade students in the Kingdom of Saudi Arabia. Methods: For achieving the purpose of the study, the descriptive analytical approach was used, by the content analysis method, and the sample consisted of the content of language activities in the" book "My Immortal Language for third intermediate grade students" in both parts (student and activity) in the first and second semesters. The list of critical thinking skills and content analysis card design was created, which included six key skills (interpretation, analysis, evaluation, conclusion, explanation, self-regulation), and falls under it (21) sub-skills. Results: The results showed that the average inclusion of critical thinking skills in the content of language activities in My Immortal Language for the third intermediate grade was (16.67%) at a "very low" level. The first-place interpretation skill was "medium" inclusion level with 41.0%, then the followed by conclusion skill at a "low" level with (26.7%). In third place was the skill of self-regulation with a "low" level with (25.4%), and the fourth was the evaluation skill with a "very low" level with 5.4%). In fifth place was the explanation skill at "very low" with (1.4%), and finally the analysis skill that was not included in the content at (0%). Conclusions: The study recommends the need to develop critical thinking skills through the content of the book's language activities in a comprehensive and balanced manner.